Alginate-Dialdehyde-Based Reporter Ink Enabling Online Detection of Matrix Metalloproteinase Activity of Encapsulated Cells - Gantert, Benedikt; Karakaya, Emine; Hofmann, Florian; Jungst, Tomasz; Meinel, Lorenz; Boßerhoff, Anja Katrin; Detsch, Rainer; Lühmann, Tessa (ACS Biomaterials Science and Engineering, 2025)
Biofabrication and three-dimensional (3D) bioprinting enable precise spatial arrangement of cells within biomaterial scaffolds. We developed an alginate-based and Förster resonance energy transfer (FRET)-responsive “turn-on” reporter ink platform to enable real-time monitoring of matrix metalloproteinase (MMP) activity. Three distinct MMP-cleavable turn-on peptide reporters were synthesized and characterized for their cell-specific cleavage profiles using recombinant MMPs, cell-derived media, and different cell cultures (NIH3T3, HEK293, and MelHo). All turn-on reporters were covalently and site-specifically incorporated into alginate dialdehyde (ADA) to yield an MMP reporter ink. The ADA reporter ink with an MMP 13 turn-on reporter was responsive to all tested cell types over time within the cast bulk constructs. The ADA reporter ink material blended with gelatin had comparable print resolution and structural fidelity as observed for ADA. The extrusion-based bioprinted MelHo cell grids, measuring 2 × 2 cm2 and containing 1 × 106 cells/mL, exhibited MMP activity responses comparable to those of the casted reporter ink system, with a 3-fold increase observed at 24 h. This study introduces a versatile, FRET-based alginate bioink platform for the real-time monitoring of MMP activities, expanding the toolkit to understand cellular performance in bioprinted 3D constructs.
CRIS-Team Scopus Importer:2025-03-28
Keywords: biofabrication; bioprinting; FRET peptide sensor; hydrogel; MMP; turn-on reporter